The Influence of Service Quality to Customer Satisfaction Toward Customer Loyalty (A Study on Customer of PT. Bank Central Asia Borobudur Branch,Malang) - Anugrah, Muhammad Fany (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims at finding out the influence of service quality on Customer Satisfaction and its influence Toward Customer Loyalty(A Study on Customers of PT. Bank Central Asia Borobudur Branch, Malang-East Java)â€.This is an explanatory research explaining the causal relationship among variables through hypotheses testing. The data collection techniques used were questionnaire and library research. This study employed 100 samples from customers of BCA Bank of Borobudur Branch Malang. The samples were taken using simple random sampling. To test the instruments, validity testing, reliability testing, and classical assumption testing were employed. The analysis method used to analyze the data was path analysis. Based on the result of the analysis, it was found out that the service quality has a direct significant influence on customers loyalty variables with tcount3.217.Next,Â the service quality also significantly influences the customers satisfaction with t countÂ 9.587.In addition, the customers satisfaction significantly influences the customers loyalty with tcount 4.762. On the other hand, service quality has an indirect influence on the customer loyalty through customer satisfaction with effect value of 0.324 on PT Bank Central Asia Tbk. Good service quality will make customers feel satisfied so that they will recommend the future customers to make use of the service from BCA Bank, say good things on the products and services given by BCA bank, and use the products from BCA bank in a long term. Keywords: Service Quality, Customer Satisfaction, Customer Loyalty